Online communities as arenas of “amateur expertise”: examples from the social media activity for justice for Roman Zadorov - Lev-On, Azi (Frontiers in Sociology, 2024)
IntroductionThis study examines online communities as arenas where diverse forms of expertise converge to influence discourse and public opinion. Using the case of social media activism advocating for justice in the wrongful conviction of Roman Zadorov for the murder of Tair Rada, it highlights how these communities serve as platforms for “professional amateurs” and demonstrates their similarities and differences from participants in the formal legal arena.MethodsThe study employs a netnographic approach to analyze seven years of social media activity across 15 Facebook groups comprising over 300,000 members. Data collection included participant observation, interviews with 25 group administrators, and thematic content analysis of posts and interactions. This methodological triangulation provides a comprehensive understanding of the discourse and dynamics within these activist communities.ResultsSix categories of experts were identified in the online discourse: 1. Court-admissible experts, including People directly connected to the case, people who are knowledgeable about the involved parties and the surrounding area, expert witnesses who are professionals testifying based on their field-specific expertise, and circumstantial witnesses who have experienced relevant events firsthand. 2. Non-court-admissible experts, including people with deep, self-taught expertise and people relying on nonrational sources, such as supernatural insights. The findings highlight the unique character of online activism as a dialogic space where conventional and unconventional forms of expertise coexist, contributing to public narratives around justice.DiscussionThe study offers a novel conceptualization of online communities as platforms for expert-driven discourse. It underscores the importance of “pro-am” expertise and symbolic capital in shaping public understanding of contentious issues. While focused on a specific legal case, the study provides broader insights into the dynamics of expertise in online activism, emphasizing the duality of court-admissible and non-court-admissible expertise. Future research should explore these dynamics across varied contexts to further understand the role of online communities in social discourse and activism.